Relaxation behavior in 0.24Pb(In1/2Nb1/2)O3–0.49Pb(Mg1/3Nb2/3)O3–0.27PbTiO3 ferroelectric single crystal. Issue 4 (March 2016) - Sun, Enwei; Qi, Xudong; Yuan, Zhongyuan; Sang, Shijing; Zhang, Rui; Yang, Bin; Cao, Wenwu; Zhao, Liancheng
Abstract: Dielectric relaxation properties of the ternary relaxor-based ferroelectric 0.24Pb(In1/2 Nb1/2 )O3 –0.49Pb(Mg1/3 Nb2/3 )O3 –0.27PbTiO3 single crystal have been investigated as a function of temperature (300–570 K) in the frequency range from 100 Hz to 100 kHz. It was found that the variation of the permittivity maximum temperature T m with frequency obeys the Vogel–Fulcher relationship. The high-temperature ( T > T m ) side of the dielectric permittivity deviated from the Curie–Weiss law, but can be described by the Lorenz-type relationship. The coercive field obtained from the polarization hysteresis loops gradually decreases with increasing temperature, and the remnant polarization persists above T m due to the existence of polar nanoregions (PNRs).